ANALISIS KEPUASAN MASYARAKAT PESERTA BJPS KESEHATAN TERHADAP PELAYANAN KESEHATAN DI UPTD PUSKESMAS TEGAL SELATAN TAHUN 2016 - Rendy Aditya Putra Armanda; Puji Astuti; Sulistyowati . (Journal of Politic and Government Studies, 2017)
ABSTRACTJKN program is organized with the aim that participants benefit health care andprotection to meet basic health needs.Basic need of health is the need for health services thatenable a sick person to recover so that he can function normally according to his age andBPJS served as the Executing Agency (Bapel). This study focused on evaluating the conductof management board of National Health Insurance Program (JKN) in UPTD SouthTegalPublic Health Center about people's satisfaction of BPJS participants to SouthTegalPublic Health Center service.The purpose of this study is to describe the satisfaction ofBPJS participant health community to health service at UPTD South TegalPublic HealthCenter Year 2016.This research is a quantitative research with cross sectional approach.Researchlocation at UPTD South TegalPublic Health center, Tegal Municipality.Subjects of researchare Public Heath Center employees and Public Health Center patients as many as 160respondents.Data collection with in-depth interviews, observation and questionnaire.Analysisof data by univariate and bivariate analysis using Chi Square statistical test.Result of research shows that tangible dimension, realibility, assurance,responsiveness and empathy have positive and significant influence to level of satisfaction ofBPJS Health participants to health service in South Tegal Public Health Center. This showsthat Patient of BPJS Health in South Tegal Public Health Center Tegal Municipality haspositive perception about tangible dimension, relibility, responsiveness, guarantee andempathy from service quality.Advised to South Tegal Public Health Center to maintain existing service qualitydimension, and improve some things that are still classified as being medium Which isexpected to become high. In some cases it has been considered to be better maintained andstill classified as moderate should be increased again, in this case there is no such thing aslow in Puskesmas Tegal Selatan. In essence, the service at Puskesmas Tegal Selatan is verygood but there is still to be improved service, so that can serve well.Keywords: public satisfaction, service quality, health services.